2016
DOI: 10.1007/s10201-016-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Water mites (Acari, Hydrachnidia) of water bodies of the Krąpiel River valley: interactions in the spatial arrangement of a river valley

Abstract: The present study is a discussion of the interactions between different types of water bodies in the spatial arrangement of a river valley, taking into account landscape data. The Hydrachnidia assemblages in particular types of valley water bodies (oxbows, riparian pools, permanent ponds, flooded alder carrs, sedge marshes, and springs) are strongly influenced by the spatial arrangement of the water bodies in the landscape. Moreover, the formation of a fauna in a particular type of valley water body is also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Miserendino et al (2011) found a relationship between land-use intensity and water quality, stream habitat and biodiversity, which in consequence affects aquatic macroinvertebrate assemblages. Stryjecki et al (2016) found that certain landscape parameters as well as spatial arrangement of the water bodies in the landscape had a strong influence on species composition and abundance of water mite fauna.…”
Section: Discussionmentioning
confidence: 97%
“…Miserendino et al (2011) found a relationship between land-use intensity and water quality, stream habitat and biodiversity, which in consequence affects aquatic macroinvertebrate assemblages. Stryjecki et al (2016) found that certain landscape parameters as well as spatial arrangement of the water bodies in the landscape had a strong influence on species composition and abundance of water mite fauna.…”
Section: Discussionmentioning
confidence: 97%
“…Following an early work by Kuehne, dated from the 1960s [16], numerous studies investigated the impacts of landscape composition and patterns on stream and lake water quality [17], even reporting that landscape characteristics are critical to water quality [18,19]. The reports evolved from cases where the relationship between the composition of landscape and the variation in water quality indicators was explored [20], to cases where the focus was moved to the spatial arrangement of the landscape (patterns) [21,22]. In the earlier studies, good water quality was generally associated with undeveloped watersheds dominated by forest land use, while poor water quality was linked to human development activities, such as agriculture [23].…”
Section: Introductionmentioning
confidence: 99%
“… Von Fumetti, Dmitrović & Pešić (2017) found that assemblages including water mites inhabiting riparian springs adjacent to higher-order streams were dominated by rhitrobionts. The dominance of lenitobionts in flooded springs is probably influenced by the spatial arrangement of water bodies in the landscape: there are numerous stagnant water bodies with a rich fauna in the Krąpiel valley ( Stryjecki et al, 2016 ). All the lenitobionts found in the springs were also present in water bodies elsewhere in the valley, but in great abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of the study area in general and the River Krąpiel in particular as well as the water bodies in the valley, are given in Stryjecki et al (2016) and Zawal et al (2017) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation